Kepemimpinan Pendidikan - Abdul Farhan; Danang Nugroho; Mochamad Izet Syahputra; Anggi Sri Mulyani; Isan Handiyana (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
To a large extent success or failure of the organization influenced by the quality of an individual in leading the chosen or assigned as the leader of a modern organization or society. Leaders in a given organization must possess the necessary qualities and abilities. Leadership takes place within an organization, a structure.Everything depends on the leader all planning will be realized if the leader can organize and direct his employees well.The author wrote this article by using references from books, journals, and articles. To achieve the research resultsThis journal was created using the literature study method only uses library sources as material.Leaders must be able to influence, organize, and encourage others involved in implementation and development of education to achieve educational or school goals effectively and efficiently is known as educational leadership. All leaders have unique ways and styles of leading. There are those that are agreeable to employees who are not. They are autocratic, laissez faire, participative, and democratic.